Highly sensitive refractive index sensing based on nanostructured porous silicon interferometers - Thuy Van, Nguyen; Thanh Son, Pham; Thanh Binh, Pham; Duc Chinh, Vu; Thi Hong Cam, Hoang; Thuy Chi, Do; Anh Tuan, Nguyen; Huy, Bui; Van Hoi, Pham (Communications in Physics, 2024)
In this study, we present the experimental evidence demonstrating the utility of electrical double layer (EDL)-induced ion accumulation, using sodium (Na+) ion in water as model substances, on a negatively charged nanostructured surface, specifically thermally grown silicon dioxide (SiO2). This novel approach, termed Ion Surface Accumulation (ISA), aims to enhance the performance of nanostructured porous silicon (PSi) interferometers in optical refractometric applications. The experimental results show that the electrical double layer-induced ion surface accumulation (EDL-ISA) on oxidized PSi interferometers enables remarkable amplification of the interferometer output signal (the spectral interferogram), even when the bulk refractive index variation is below 10-3 RIU. This substantial signal enhancement translates into an increase in sensitivity of up to two orders of magnitude, facilitating the reliable measurement of refractive index variations with both a detection limit (DL) and resolution (R) as low as 10-4 RIU. This achievement elevates the performance of PSi interferometers in photonics and plasmonics-based refractive index platforms.